Scientific-Theoretical Psychological Analysis of Personal Activity Motivation (Zien Journal of Social Sciences and Humanities, 2022)
The role and importance of motivation in personal activity is detailed in this article. A scientific theoretical psychological analysis of personal activity motivation was presented, and an attempt was made to reveal the essence of opinions and approaches expressed by our scientists through motivation theories